Assessing biodiversity in LULUCF-CDM projects: towards synergizing UNFCCC and CBD - Murdiyarso, Daniel (Organizing Comittee of the International Symposium/Workshop on the Kyoto Mechanism and the Conservation of Tropical Forest Ecosystem, 2004)
The ultimate goal of the United Nations Framework Convention on Climate Change (UNFCCC) is to stabilize the concentrations of greenhouse gas in the atmosphere at a level that would prevent dangerous anthropogenic interference with the climate system. From a sustainable development point of view the implementation of Clean Development Mechanism (CDM) in forestry sector, under the Kyoto Protocol to the UNFCCC, has been viewed as reducing the opportunity to promote clean energy technology. It is also considered to promote clearing of the existing natural forests while introducing large-scale mono-species plantations which will threaten the biodiversity conservation. Hence, it may conflict with the objectives of the Convention on Biological Diversity (CBD). Synergizing the UNFCCC and the CBD require linking their provisions on sustainable forestry, adaptation measures, monitoring and environmental impact assessment. These steps would eventually lead to joint efforts between the two conventions to (1) analyze the impacts of climate change on biological diversity and (2) integrate biodiversity consideration in the implementation of land-use and land-use change (LULUCF) activities under CDM to mitigate climate change or adaptation measures. It is extremely important that the reporting systems under the two conventions facilitate such effort prior to the first commitment period of the Kyoto Protocol. Subsidiary bodies of the conventions should be able to provide technical advices to the Conference of Parties, especially that serves as meeting of the Parties to the UNFCCC. The instruments and tools to address and resolve the conflicts under both conventions have to be developed and applied in the implementation of LULUCF CDM projects. There are several on-going international processes on criteria and indicators for sustainable forest management. These are implemented at various level and forest types through multilateral processes. Single and multiple criteria and numerous indicators ranging from seven to 65 have been adopted with main challenges in accommodating local concerns in multilateral processes. The Center for International Forestry Research (CIFOR) developed a generic template of criteria and indicators (C&I) which can be used to assess the sustainability of forest management. Maintenance of biodiversity and ecosystem function in management units are among the criteria used with seven and five indicators respectively. In addition, maintenance of genetic variation is also introduced as criteria with four indicators. CIFOR's C& I was tested at various management units across tropical ecosystem sites to determine their suitability. This experience can potentially be useful in LULUCF-CDM projects.